An Analysis of Discussions on Academic Dishonesty in Journalism & Mass Communication Educator, Volumes 1 Through 74. (December 2020) - Auger, Giselle A.; Waters, Richard D.
Research has shown that professionals who act unethically in the workplace likely have an academic background with academic dishonesty violations. Given that understanding and teaching academic honesty behaviors are critical to best prepare future media professionals, this research examines discussions of academic dishonesty in Journalism & Mass Communication Educator 's ( JMCE ) 74 volumes to understand what topics emerge as guiding the discussion. Through a qualitative content analysis using emergent design, 14 JMCE articles are compared with 53 Communication and Mass Media Complete database articles to identify trends and needs for future research of the topic.